The Association Between Conformity to Masculine Norms and Alexithymia Among Men - Gene Meshani; Andreas Corsini Widya Nugraha; Arfian (Yayasan Yusda Edu Indonesia, 2026)
Alexithymia is a difficulty in recognizing, understanding, and expressing emotions. One factor that is assumed to be related to alexithymia in men is conformity to masculine norms. This study aims to examine the relationship between conformity to masculine norms and alexithymia among male technicians at PT X. This research employed a quantitative approach with a correlational design. The sample consisted of 155 male technicians selected using purposive sampling. Data were collected using the Toronto Alexithymia Scale (TAS-20) and the Conformity to Masculine Norms Inventory (CMNI-30), and were analyzed using Pearson correlation analysis. The results showed a significant positive relationship between conformity to masculine norms and alexithymia. These findings indicate that the higher the conformity to masculine norms, the higher the tendency for individuals to experience alexithymia. Thus, conformity to masculine norms is one of the factors associated with the emergence of alexithymia among male technicians.